Hubungan Pengetahuan, Sikap dan Pendidikan Ibu dengan Pemberian ASI Eksklusif pada Ibu yang Memiliki Bayi Usia Lebih dari 6 Bulan di Wilayah Kerja Puskesmas Gandus Tahun 2021 - Lily Marpika; Helni Anggraini; Anur Rohmin; Siti Amallia (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Exclusive breastfeeding is the best food given to babies during the age of 0-6 months without being interspersed with other additional food. However, in reality, there are still many breastfeeding mothers who do not provide exclusive breastfeeding to their babies due to various factors. In Indonesia, mothers who exclusively breastfeed their babies during the current month are still low, which is 2% of the total number of mothers who give birth. The behavior of breastfeeding mothers is based on Lawrence Green's (1980) behavioral theory, namely predisposing factors (knowledge, attitudes, education level, and work), enabling factors (family economic level), and reinforcing factors (family role). This study was conducted to see the various factors associated with low exclusive breastfeeding in infants in Gandus District. This study used descriptive analytic method with cross sectional approach, where the sample was 100 breastfeeding mothers. Sampling using Random Sampling method, namely Proportioned Stratified Random Sampling. The instrument in this study used a questionnaire. Data processing using manual system was done by univariate and bivariate analysis with Chi-Square test with level of sgnificant (alpha) 0.05. From the results of the study it is known that the value of x2 count is greater than x2 table for work (4.06> 2.71), so there is a significant relationship between work and low exclusive breastfeeding. While the x2 value is smaller than the x2 table (knowledge (1.43 < 2.71), attitude (0.34 < 2.71), education level (0.10 < 4.61), family economic level (0.44 < 2.71), and family peren (0.58 < 2.71), so there is no significant relationship with the low exclusive breastfeeding in infants. The suggestion from this study is that all parties involved in exclusive breastfeeding in infants can make various efforts to increase knowledge and awareness that are adjusted to all the resources available in the area.